Analisis Penggunaan Pembayaran Digital di Elora Coffe and Roastery - Tomi Sianipar; Tito Pratama; Dailami .; Natal Olotua Sipayung (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyze the implementation of the digital payment system at Elora Coffee and Roastery Batam Center. Elora Coffee was chosen as the research site because it has fully adopted a cashless payment system and is recognized as one of the most popular cafés in Batam with a high number of visitors, making it a potential and relevant location for the study. The research is motivated by the rapid growth of financial technology, which has become an integral part of modern economic activities and lifestyles. This study employs a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and documentation involving ten selected customers as respondents. The findings indicate that the implementation of digital payment at Elora Coffee operates effectively and is perceived as easy to use, fast, secure, and efficient. Moreover, the use of digital payment systems enhances Elora Coffee’s image as a modern café that is adaptive to technological advancement and innovation.